Recognition of Deformed Familiar Faces: Contrast Negation and Nonglobal Stretching. (October 2019) - Sandford, Adam; Rego, Skylar
Familiar face recognition is robust to subtle and drastic changes in appearance. Knowing which conditions harm our recognition highlights underlying processes that have prominent roles in face learning. Here, we focused on two image deformations that studies suggest independently harm recognition: contrast negation and stretching of top or bottom halves of a face orthogonal to the unstretched half (nonglobal stretching). Participants were asked to categorize self-reported familiar or unfamiliar faces presented in photographic positive and negative in a fully within-subjects design. In Experiments 1 and 2, recognition of contrast-positive faces was robust to global and nonglobal stretching, suggesting iso-dimension ratios do not have a role in familiar face recognition. However, performance was consistently impaired by contrast negation in all configurational conditions. Further reductions in categorization accuracy when top halves of contrast-negated faces are stretched suggest some limited role for configuration under these image conditions. In Experiment 3, presenting the top or bottom half of nonglobal stretch conditions suggested categorization of nonglobal stretch faces did not require perception of the whole face, in the research design reported here. These results highlight further limits to configurational accounts of face recognition and indicate a relatively important role for surface reflectance cues.